The Application of Micro-Teaching Method in the Development of Physics Teaching Competence for Continuing Mathematics Pedagogical Students of Savannakhet Teacher Training College - LASASAN, Insong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This study aimed to promote: 1) to develop the physics teaching competence (PTC) by applying of micro-teaching method to achieve 70% or more; 2) to study the development level of PTC by applying of micro-teaching method; 3) to study the relationship between the competence of designing physics teaching lesson plan (CDPTLP) and the competence of implementing physics teaching lesson plan (CIPTLP). The target group was 16 math continuing program pedagogical students (MCPPS) in the 2021 - 2022 academic year. The study employed one group posttest only time series design. The researchers proposed the structure of PTC, some measures to develop and assess the PTC of MCPPSs include: Students learn theories about developing and assessing the PTC according to Micro-teaching method; Students practice to develop and assess of each expressive behavior of each component competence; Students practice to develop proficiency in component competences of PTC and final exam. The assessment results of the development level of each component competence of pedagogical students from the first phase to the last phase shown that: the CDPTLP in the last phase (mean of 7.97 and SD of 0.89) was statistically significantly higher than in the first phase (mean of 6.90 and SD of 0.79) at the 95% confidence level, the development levels percentage of this component competence was 79.68% and the normalized gain <g> was 0.38 which was classified in medium gain; the CIPTLP (mean of 7.79 and SD of 1.00) higher than in the first phase (mean of 6.63 and SD of 1.00), the development levels percentage of this component competence was 77.89% and the normalized gain <g> was 0.34 which was classified in medium gain; the competences of assessing the implementing for practicing to develop the PTC (mean of 8.02 and SD of 0.98) higher than in the first phase (mean of 6.90 and SD of 0.86), the development levels percentage of this component competence was 80.16% and the normalized gain <g> was 0.36 which was classified in medium gain. The result verified that applying of micro-teaching method in teaching – learning of Physics teaching method subject was effective to develop the PTC of MCPPSs. For the relationship bitween the CDPTLP and CIPTLP in each phase was a strong positive relationship (phase 1 , phase 2 and phase 3 ) at the 99% confidence level. The result verified that the CDPTLP and CIPTLP have a relationship and can vary from field to field.